Gut-Immune-Kidney Axis: Influence of Dietary Protein in Salt-Sensitive Hypertension. Issue 11 (19th August 2022) - Mattson, David L.; Dasinger, John Henry; Abais-Battad, Justine M.
Abstract : Humans with salt-sensitive hypertension demonstrate increased morbidity, increased mortality, and renal end-organ damage when compared with normotensive subjects or those with salt-resistant hypertension. Substantial evidence from humans and animals has also demonstrated the role of dietary components other than salt to modulate hypertension. Evidence presented in this review provides support for the view that immunity and inflammation serve to amplify the development of salt-sensitive hypertension and leads to malignant disease accompanied by end-organ damage. Interestingly, salt-sensitive disease is modulated by changes in dietary protein intake, which also influences immune mechanisms. Together, the evidence presented in this review from animal and human studies indicates that changes in dietary protein source have profound effects on the gut microbiota, microbiota-derived metabolites, DNA methylation, gene expression, immune cell activation, the production of cytokines and other factors, and the development of salt-sensitive hypertension and related disease phenotypes.